Description of a new species of Hamamelistes forming galls on Fothergilla spp. (Hamamelidaceae) and the generic limits of Hormaphidini (Sternorrhyncha: Aphididae: Hormaphidinae) - Dederich, Ashley E.; Halbert, Susan E.; Von Dohlen, Carol D. (Zootaxa, 2022)
Hamamelistes and Hormaphis aphids of the tribe Hormaphidini are distributed disjunctly in eastern North America and Eurasia. Host-alternating species have life cycles encompassing generations in a gall on witch-hazel (Hamamelis spp.) and generations on leaves of birch (Betula spp.). In Hamamelistes, generations on witch-hazel induce globular pouch galls on flower or leaf buds. Herbarium specimens of a related Hamamelidaceae genus, Fothergilla, contain large galls in place of the seed head. We obtained a fresh sample of these elongate pouch galls collected from F. milleri in Alabama, USA. The galls were formed in place of fruiting structures and contained numerous aphids. Examination of morphology and the cytochrome oxidase subunit I “barcode” DNA sequence confirmed that the aphids are an undescribed species of Hamamelistes. Here, we describe the new species, Hamamelistes blackmani Dederich & von Dohlen sp. n., from the morphology of foundresses, immatures, and winged forms in the gall. The life cycle is presumed monoecious. In addition, we review the evidence for including other genera in Hormaphidini and recommend that this tribe be restricted to Hamamelistes and Hormaphis.